Influence of Visuals on Consumer preference in Restaurants: Structure Equation Modelling Analysis - Neema, A; Bapna, I (International Journal of Computer Sciences and Engineering, 2025)
Neuromarketing, as a scientific discipline in the field of marketing research, represents an implementation of neuroscientific methods, with a purpose of a better understanding of human behavior. This paper aimed at identifying the influence of visuals (what one see) on consumer preference in 3 star and above rating restaurants in Indore (Madhya Pradesh). The purpose of this study is to understand the current characteristic of visuals that is used in restaurants. It also seeks to understand the role of visuals to shape up consumer preference in restaurant industry. A sample of 100 consumers was taken who usually visited multi cuisine restaurants in Indore. Data was collected through a well-structured questionnaire and analyzed through SEM (structure equation modeling). This study will propose important implication for practitioners and academicians.